Olfactory bulb encoding during learning under anesthesia - Nicol, Alister U.; Sanchez-Andrade, Gabriela; Collado, Paloma; Segonds-Pichon, Anne; Kendrick, Keith M. (Frontiers in Behavioral Neuroscience, 2014)
Neural plasticity changes within the olfactory bulb are important for olfactory learning, although how neural encoding changes support new associations with specific odours and whether they can be investigated under anaesthesia, remain unclear. Using the social transmission of food preference olfactory learning paradigm in mice in conjunction with in vivo microdialysis sampling we have shown firstly that a learned preference for a scented food odour smelled on the breath of a demonstrator animal occurs under isofluorane anaesthesia. Furthermore, subsequent exposure to this cued odour under anaesthesia promotes the same pattern of increased release of glutamate and GABA in the olfactory bulb as previously found in conscious animals following olfactory learning, and evoked GABA release was positively correlated with the amount of scented food eaten. In a second experiment, multiarray (24 electrodes) electrophysiological recordings were made from olfactory bulb mitral cells under isofluorane anaesthesia before, during and after a novel scented food odour was paired with carbon disulfide. Results showed significant increases in overall firing frequency to the cued-odour during and after learning and decreases in response to an uncued odour. Analysis of patterns of changes in individual neurons revealed that a substantial proportion (>50%) of them significantly changed their response profiles during and after learning with most of those previously inhibited becoming excited. A large number of cells exhibiting no response to the odours prior to learning were either excited or inhibited afterwards. With the uncued odour many previously responsive cells became unresponsive or inhibited. Learning associated changes only occurred in the posterior part of the olfactory bulb. Thus olfactory learning under anaesthesia promotes extensive, but spatially distinct, changes in mitral cell networks to both cued and uncued odours as well as in evoked glutamate and GABA release.